Efeito de níveis de fósforo no crescimento inicial, biomassa e atividade in vivo da fosfatase ácida em Lychnophora ericoides Mart - Maia-Almeida, C. I. [UNESP]; Paron, M. E. [UNESP]; Cézar, V. R S; Fernandes, Dirceu Maximino [UNESP]; Fernandes, L. A.; Ming, Lin Chau [UNESP] (My University, 2008)
The effect of phosphorus levels on seedling growth, dry and fresh matter production, and in vivo acid phosphatase activity was studied in Lychnophora ericoides cultivated during 130 days after transplanting in a greenhouse. Experimental design was completely randomized, with four P 2O 5 levels (0; 40; 80; 160 mg dm -3 as triple superphosphate) and five replicates of four plants each. The used soil was dystrophic acid dark red latosol. Lychnophora ericoides is responsive to phosphate fertilization with modification in daily relative growth rate, dry matter production and distribution among the plant parts. Acid phosphatase activity had significant and negative correlation with total, leaf and stem dry matter production, as well as with P levels accumulated in the leaf tissue. On the other hand, acid phosphatase activity had significant and positive correlation with root/shoot ratio.
Effect of phosphorus levels on initial growth, phytomass and in vivo acid phosphatase activity in Lychnophora ericoides Mart
Keywords: Arnica; Brazilian native plants; Extinction; Medicinal plants; Plant nutrition; acid phosphatase; calcium; phosphate; phosphorus; potassium; enzyme activity; fertilization; greenhouse; in vivo study; Lychnophora ericoides; medicinal plant; nonhuman; plant growth; plant leaf; plant stem; seedling